STUDY OF CLINICAL, LABORATORY, AND IMMUNOLOGICAL FEATURES IN PATIENTS WITH BRONCHOPULMONARY DISEASES - Kalandarova D.O (TADQIQOTLAR, 2026)
Abstract. Bronchopulmonary diseases remain a significant medical problem due to their chronic course and frequent complications. This study evaluates clinical manifestations, laboratory findings, and immunological parameters in patients with bronchopulmonary pathology. The analysis focused on inflammatory activity, hematological changes, and immune system responsiveness. The findings demonstrate that early inflammatory responses and immune imbalance are common even in the initial stages of the disease, highlighting the importance of timely diagnosis and individualized treatment strategies. Diseases of the bronchopulmonary system, such as chronic bronchitis, pneumonia, and bronchial asthma, are widely prevalent and often associated with immune dysfunction and recurrent infections. The chronic nature of these conditions contributes to persistent inflammatory processes and alterations in the body’s defense mechanisms. Recent studies suggest that immunological disturbances play a key role in disease progression. Therefore, a comprehensive evaluation of clinical, laboratory, and immune parameters is essential for improving diagnostic accuracy and therapeutic outcomes. The aim of this study was to assess clinical, laboratory, and immunological changes in patients with bronchopulmonary diseases and to formulate evidence-based recommendations for optimizing diagnostic and treatment approaches. The study involved 120 patients diagnosed with bronchopulmonary pathology who received inpatient treatment between 2022 and 2024. The control group included 30 apparently healthy individuals. Clinical assessment was combined with laboratory investigations, including complete blood count and biochemical analysis, as well as immunological evaluation of CD4+, CD8+, IgA, IgM, and IgG levels. Statistical processing was carried out using SPSS software, applying Student’s t-test, χ² test, and correlation analysis.